Assessing the Constraints to the Adoption of Containerized Agriculture in Northern Canada - Natcher, David; Ingram, Shawn; Solotki, Ray; Burgess, Carl; Kulshreshtha, Suren; Vold, Lindsey (Frontiers in Sustainable Food Systems, 2021)
Considerable advancements are being made in containerized agricultural systems in the northern Canada. These systems are proving successful at overcoming the environmental constraints associated with cold climate food production and hold great promise for remote communities that suffer from high rates of food insecurity. However, if new technologies are to provide lasting and meaningful change for northern communities, critical attention needs to be directed to the variable and complex constraints that may limit their adoption and scalable success. To evaluate the potential uptake and use of containerized agriculture in northern Canada we employed the Adoption and Diffusion Outcome Prediction Tool. Twenty-two variables were ranked according to their influence on adoption. Six variables were then identified as being most constraining to the adoption of containerized agricultural systems, including upfront costs, expected profits, environmental impacts, complexity of the technology, trialability, and reversibility. We believe this type of pre-assessment is a critical, yet often over-looked step in technology transfer, and a necessary stage in assessing the scaling out potential for new food production technologies. This is particularly important for new food production technologies that demand significant financial investments that are wholly or partially irreversible.